Comparative ARPES studies of LaOxF1−xBiS2 (x = 0.23 and 0.46). (January 2016) - Terashima, K; Wakita, T; Sunagawa, M; Fujiwara, H; Nagayama, T; Ono, K; Kumigashira, H; Nagao, M; Watauchi, S; Tanaka, I; Okazaki, H; Takano, Y; et al.
Abstract: BiS2 -based layered superconductors are new superconductors, having been paid special attention due to the layered crystal structure and the characteristic electronic structure that can lead to exotic mechanism of superconductivity as well as cooperation of superconductivity and ordered phases. In this article, we report valence band dispersions and Fermi surface topology of LaO1-x Fx BiS2 ( x = 0.23, Tc < 2 K) studied by angle-resolved photoemission spectroscopy, and compared them with those of LaO1-x Fx BiS2 ( x = 0.46, Tc = 3.1 K). We discuss experimental x dependent electronic structures and its relation to Tc . We also point to anomalous spectroscopic features in LaO1-x Fx BiS2 ( x = 0.46) that can be explained by band structure calculations considering distorted lattice, suggesting role of dynamical or static lattice distortion to the physical properties.